2019
DOI: 10.1007/s10822-019-00236-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic-field and surface-shape similarity for virtual screening and pose prediction

Abstract: We introduce a new method for rapid computation of 3D molecular similarity that combines electrostatic field comparison with comparison of molecular surface-shape and directional hydrogen-bonding preferences (called “eSim”). Rather than employing heuristic “colors” or user-defined molecular feature types to represent conformation-dependent molecular electrostatics, eSim calculates the similarity of the electrostatic fields of two molecules (in addition to shape and hydrogen-bonding). We present detailed virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 38 publications
(63 reference statements)
0
71
1
Order By: Relevance
“…Partial atomic charges are real numbers assigned to individual atoms of a molecule that approximate the distribution of electron density among these atoms. Partial atomic charges find many applications in computational chemistry [ 1 3 ], chemoinformatics [ 4 6 ], bioinformatics [ 7 , 8 ], and nanoscience [ 9 , 10 ]. Because the charges are not physicochemical observables but a theoretical concept, many methods for their calculation have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Partial atomic charges are real numbers assigned to individual atoms of a molecule that approximate the distribution of electron density among these atoms. Partial atomic charges find many applications in computational chemistry [ 1 3 ], chemoinformatics [ 4 6 ], bioinformatics [ 7 , 8 ], and nanoscience [ 9 , 10 ]. Because the charges are not physicochemical observables but a theoretical concept, many methods for their calculation have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of fedratinib suggests that it should have a different pharmacological profile compared to those of ruxolitinib and baricitinib. Some theoretical findings are validated through the reported biological activities associated with these drugs ( Table 1 ), [ 37 , 38 , 39 , 40 , 41 ]. In conclusion, both ruxolitinib and baracitinib may represent promising options for COVID-19 treatment; however, the clinically reported adverse effects of these drugs and our theoretical calculations, especially for fedratinib, raise an alarming concern regarding their safety.…”
Section: Pre-clinical Studiesmentioning
confidence: 85%
“…Structural overlay between these molecules indicated that the similarity between ruxolitinib and baricitinib is 82.5%, whereas fedratinib highly deviates from ruxolitinib and baricitinib. Similarity and alignments were measured based on molecular fields descriptors generated by Cresset’s FieldAlign Software (version 1.0.2), ( Figure 5 ), [ 37 ]. This theoretical finding indicates that these two molecules might share similar pharmacological and adverse effects.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are subdivided into two categories: (1) alignment-free methods that are usually computationally faster because they do not require overlapping the molecules or evaluating properties related to the surface (Seddon et al, 2019 ) and (2) alignment-based methods that are computationally costly since these methods superimpose molecular shapes and analyze surface properties, such as polarity and hydrophobicity (Fontaine et al, 2007 ; Kumar and Zhang, 2018 ). Different methods have been used in the representation of the 3D molecular shape of the ligands, such as Gaussian overlay-based methods (Cai et al, 2013 ), atomic distance-based methods (Ballester et al, 2009 ; Ballester, 2011 ; Bonanno and Ebejer, 2020 ), and surface-based methods (Karaboga et al, 2013 ; Cleves et al, 2019 ). The recognized molecular shapes are transformed into the 3D molecular fingerprints that are then compared using similarities or distance indexes, such as Tanimoto, Dice, and Tversky coefficients (Shin et al, 2015 ).…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%